Efectos proteolitico, hemorragico y mionecrotico de los venenos de serpientes costarricenses de los generos Bothrops, Crotalus y Lachesis - Gutiérrez, José María (1980)
We studied the proteolytic, hemorrhagic and myonecrotic activities of ten Costa Rican species of snakes from the family Viperidae. All of them showed these three activities but we did not observe any correlation between their relative magnitudes. The most myonecrotic venoms were Bothrops asper and B. schlegelii; the most hemorrhagic was B. picadoi and the strongest proteolytic activity using casein was in the venoms of B. godmani and B. lateralis. The lethality of these venoms correlated with the magnitude of tissue destruction observed microscopically. The histopathological analysis showed two kinds of necrosis: either a myolitic necrosis or a mixed necrosis, with both myolitic and coagulative areas. All the histological slides showed a strong hemorrhagic action, a polymorphonuclear leucocyte rich exudate and some vascular alterations such as angionecrosis and thrombosis.